A method for the biological age of the heart determination - L. A. Bodretska; I. S. Shapovalenko; A. V. Pisaruk; I. A. Antoniuk-Shchehlova; O. V. Bondarenko; S. S. Naskalova; V. B. Shatylo (Zaporožskij Medicinskij Žurnal)
Determination of the human heart biological age (BA) is relevant for timely stratification of the risk of developing diseases, prevention, control of individual aging rate and geroprotective therapy.